Формирование базы данных термодинамических свойств сложных эфиров жирных кислот биодизельных топлив в газовой фазе (часть 1) - Левтеров, Антон Михайлович; Левтеров, Александр Антонович; Левтерова, Людмила Ивановна (НТУ "ХПИ", 2016)
Анализ научных публикаций позволил обусловить набор расчетных и экспериментальных выборок, которые дают возможность сформировать базу данных о термодинамических и термохимических свойствах сложных метиловых и этиловых эфиров высших жирных кислот, химически связанных в различных комбинациях в биодизельных топливах, производимых из растительных масел. Такая база данных позволит реализовать численное моделирование рабочих процессов поршневых двигателей с самовоспламенением, работающих как на чистом биодизельном топливе, так и на бионефтяных композициях.

The share of alternative fuels from biological raw materials (ethanol, the biodiesel) in the balance of motor fuels increases constantly. A set of data on thermodynamic and thermal properties of these fuels is required for a comprehensive research of the working processes of piston engines. The properties of ethanol are well known and have been successfully used in experimental and numerical researches. The physical and chemical properties of biodiesel are studied and known, so there are no obstacles for experimental research of biodiesel-fired engines. These questions have been the subject of many scientific articles. Difficulties arise in the numerical simulation of workflows that require data on the thermodynamic characteristics of the high-temperature components of this fuel. The known thermodynamic databases do not contain such information. Therefore, the description of the combustion process has been maximally simplified.
Forming database of thermodynamic properties of fatty acid esters of biodiesel fuel in the gas phase (part 1)
Keywords: биотоплива; растительные масла; математическое моделирование; рабочий процесс; термохимические свойства; полином; biofuels; fatty acid esters; vegetable oils; mathematical modeling